Prevention and treatment of emergencies in thyroid patients - Anatoliy Filippovich Romanchishen; Irina Yur'evna Kim; Aleksandr Aleksandrovich Bogatikov (Эндокринная хирургия, 2015)
Aim To evaluate the surgical treatment outcomes for patients with acute complications of thyroid disease (compression syndrome, early postoperative complications - like bilateral recurrent laryngeal nerve injure, bleeding (PB) in thyroid bed and others) performed in the single medical center. Material and methods Anaplastic Thyroid Cancer (243 patients), multiglandular retrosternal goiter (25 cases), and purulent acute thyroiditis (9 observations) made heavy compression of neck and mediastinal aerodigestive organs and were the reason for emergent thyroid surgery. Were estimated intraoperative recurrent nerve (RLN) injures consequences and postoperative bleeding, made necessary for reoperations after 25663 thyroid surgeries during 36 years of the Center practice. Results Surgical intervention for Anaplastic Thyroid Cancer in all of patients has got palliative character only. Postop. lethality rate made 21,0% after emergency interventions, and 2,5% - after routine procedure. Combinations of it with radiochemotherapy has prolonged survival rate up to 13 month in 25% of cases. Follow up results of thyroid surgery in 23777 patients has found unexpected and relevant unilateral RLN injures in 251 (1.0%) and bilateral – in 91 (0.38%) cases. Recurrent laryngeal nerves and larynges reconstruction surgery allow us to decanulate more that 75% those patients. Postoperative bleeding (PB) and thyroid bad hematomas were found in 138 больных (0.58%) patients. The most often PB happened in initial and recurrent DTG (1.07%, 0.94%), TC (0.82%) patients. In most (65.5%) of cases PB began during the first 6 hours. In case of PB we parted wound edges anywhere, intubated repeatedly trachea, inspected wound; performed hemostasis and drained wound. Main sources of PB were inferior (40.38%) or superior (17.30%) thyroid artery. Source was not found in 13.35%. PB prevention included: careful hemostasis with control lavage of the wound; fascia covering of the thyroid bed and high pressure test,  ligation of inferior thyroid artery in doubtful cases. Conclusion Thyroid Surgery needs precise knowledge of skull base, neck and mediastinum anatomy, safety resection of thyroid, parathyroid, under RLN visual control, thorough hemostasis and closely postoperative watching for patients.